Use of transgenic GFP reporter strains of the nematode Caenorhabditis elegans to investigate the patterns of stress responses induced by pesticides and by organic extracts from agricultural soils - Anbalagan, Charumathi; Lafayette, Ivan; Antoniou-Kourounioti, Melissa; Gutierrez, Carmen; Rodriguez Martin, Jose; Chowdhuri, Debapratim Kar; de Pomerai, David I. (Springer, 2013)
As a free-living nematode, C. elegans is exposed to various pesticides used in agriculture, as well as to persistent organic residues which may contaminate the soil for long periods. Following on from our previous study of metal effects on 24 GFP-reporter strains representing four different stress-response pathways in C. elegans (Anbalagan et al. 2012), we now present parallel data on the responses of these same strains to several commonly used pesticides. Some of these, like dichlorvos, induced multiple stress genes in a concentration-dependent manner. Unusually, endosulfan induced only one gene (cyp-34A9) to very high levels (8-10-fold) even at the lowest test concentration, with a clear plateau at higher doses. Other pesticides, like diuron, did not alter reporter gene expression detectably even at the highest test concentration attainable, while others (such as glyphosate) did so only at very high concentrations. We have also used five responsive GFP reporters to investigate the toxicity of soil pore water from two agricultural sites in south-east Spain, designated P74 (used for cauliflower production, but significantly metal contaminated) and P73 (used for growing lettuce, but with only background levels of metals). Both soil pore water samples induced all five test genes to varying extents, yet artificial mixtures containing all major metals present had essentially no effect on these same transgenes. Soluble organic contaminants present in the pore water were extracted with acetone and dichloromethane, then after evaporation of the solvents, the organic residues were redissolved in ultrapure water to reconstitute the soluble organic components of the original soil pore water. These organic extracts induced transgene expression at similar or higher levels than the original pore water. Addition of the corresponding metal mixtures had either no effect, or reduced transgene expression towards the levels seen with soil pore water only. We conclude that the main toxicants present in these soil pore water samples are organic rather than metallic in nature. Organic extracts from a control standard soil (Lufa 2.2) had negligible effects on expression of these genes, and similarly several pesticides had little effect on the expression of a constitutive myo-3::GFP transgene. Both the P73 and P74 sites have been treated regularly with (undisclosed) pesticides, as permitted under EU regulations, though other (e.g. industrial) organic residues may also be present.